Analisis Strategi Marketing dalam Meningkatkan Volume Penjualan pada Es Teh Indonesia di Cabang Sepanjang, Kab. Sidoarjo - Larissa Diva Nabilah; Budi Prabowo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research was conducted with the aim of understanding the marketing strategies used by Es Teh Indonesia in Sepanjang Branch, Sidoarjo Regency, with a focus on increasing sales volume. This research adopted a descriptive qualitative approach as the methodology. The research location includes Es Teh Indonesia Sepanjang Branch, Sidoarjo Regency, and the participants involve the owner, employees, and consumers of the branch. The data analysis approach applied in this research is SWOT analysis, which is implemented through EFAS and IFAS tables. The results of the research analysis using IFAS and EFAS, the Indonesian Ice Tea business in Sepanjang Branch, Sidoarjo Regency has a strength factor with a total score of 2.73, while the weakness factor gets a total score of 0.40. Opportunities receive a total score of 1.85 and threats have a total score of 0.45. Based on the results of the SWOT diagram, Es Teh Indonesia is in quadrant 1, which supports an aggressive strategy (Growth oriented strategy). By referring to the SWOT diagram and matrix, the resulting strategy is the SO strategy because it has the highest score. The SO strategy supports aggressive growth (growth-oriented strategy). During the growth phase, the company can implement various strategies to maintain market growth.